Comparison the effect of aqueous leaves extract of Melia azedarach L. and Anastatica hierochuntic with antibiotic (Enrofloxaccin) on some blood and biochemical traits of broiler: Z. T. M. AL-Dhanki and A. A. Al-Hamadani - ضنكي زيادطارق محمد (The Iraqi Journal of Veterinary Medicine, 2012)
This experiment were conducted to compare the effect of aqueous leaves extract of Melia azedarach and Anastatica hierochuntic with the antibiotic (Enrofloxaccin) for 49 days, 270 chicks one day old (Ross 308) were randomly distributed into 6 treatments with 3 replicates per treatment and 15 chicks per replicate (45 chicks/treatment). The first treatment were the control, antibiotic (enrofloxaccin) were used in the second treatment at rate of 0.5 ml per liter of tap water, in the 3rd and 4th treatment the aqueous leaves extract of Anastatica hierochuntic were used at rate of 10 and 15 mg/L respectively, and in the 5th and 6th treatment the aqueous leaves extract of Melia azedarach were used at rate of 10 and 15 mg / ml resp. At the end of experiment, blood samples were collected for whole blood tests; Red and White Blood Cells count, biochemical serum tests were also involved ; the concentrate of total cholesterol, glucose, and total protein. The Data showed that using aqueous leaves extract of Anastatica hierochuntic at rate of 10 and 15 mg/L leading to significant increase in serum cholesterol concentration , while , protein serum concentration were significantly decreased in control and in 6th treatment where the aqueous extract of Melia azedarach were used at rate of 15 mg /ml , and there is no significant differences between the treatments in RBC , WBC count , and glucose concentration